Pengoptimalisasi Potensi Sumber Daya Manusia Dalam meningkatkan Kesejahteraan Pelaku UMKM Melalui Teknologi - Ni Made Satya Utami; Ni Putu Tia Damayanti (PT. Karya Inovatif Nusantara, 2024)
Every business must experience volatile sales. The decline in sales is caused by many factors, one of which is the promotional factor. Where the lack of promotion can make sales decline because fewer people know about the business being undertaken. Because promotion is a very decisive and integral part of the success of a business. One promotion that is often used by business people and gets very fast feedback is social media promotion. Service objectives implemented in Njs. Projects to conduct training optimization of promotion through social media and assistance in helping create product catalogs on Instagram as well as assistance in making catalog wrapping to make it easier for buyers to choose their orders and assist employees in explaining and recording orders by the wishes of buyers. The method of Service is by PRA (Participatory Rural Appraisal) which involves the participation of Njs. employees. Projects. The result of devotion in Njs. Projects and MSME actors experienced a very rapid increase in income, and the number of orders increased even higher, because of the success in using technology such as social media as a promotional Medium. In addition, the work of employees can be more efficient and effective with product catalogs and wrapping to minimize errors in recording orders of prospective buyers.